Beliefs and Practices on Translanguaging Among Pre-Service Teachers in Mindanao State University - Marawi - Joross Michael Bongcarawan; Sittie Ainah Capal (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2024)
This study aimed to examine the beliefs and practices of pre-service English teachers concerning translanguaging within the context of the Philippines. Guided by the frameworks of Translanguaging Theory and Common Underlying Proficiency Theory, the research involved twenty-four pre-service teachers from Mindanao State University – Marawi, who participated by completing a survey questionnaire administered through convenience sampling. Utilizing a quantitative research design, the study systematically analyzed data from the Likert-scale questionnaire by creating charts and tables that detailed frequency and percentage distributions. The key findings showed a significant majority of participants held strong beliefs in the effectiveness of translanguaging within educational contexts. Furthermore, they recognized the importance of employing translanguaging for various contexts and purposes. Given their strong convictions about the benefits of translanguaging, these pre-service English teachers are likely to incorporate translanguaging strategies into their pedagogical approaches, which can enhance the educational experience for both teaching and learning. By understanding and embracing translanguaging practices, future educators may foster more inclusive and effective classroom environments that leverage their students' linguistic resources. This study not only fills a gap in the existing research on translanguaging in the Philippine educational landscape but also highlights its potential to improve educational outcomes for bilingual learners.